2021
DOI: 10.3390/cells10051235
|View full text |Cite
|
Sign up to set email alerts
|

To Ubiquitinate or Not to Ubiquitinate: TRIM17 in Cell Life and Death

Abstract: TRIM17 is a member of the TRIM family, a large class of RING-containing E3 ubiquitin-ligases. It is expressed at low levels in adult tissues, except in testis and in some brain regions. However, it can be highly induced in stress conditions which makes it a putative stress sensor required for the triggering of key cellular responses. As most TRIM members, TRIM17 can act as an E3 ubiquitin-ligase and promote the degradation by the proteasome of substrates such as the antiapoptotic protein MCL1. Intriguingly, TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 157 publications
(308 reference statements)
1
8
0
Order By: Relevance
“…Indeed, Trim17 reduces the interaction between Trim39 and NFATc3, as determined by both co-IP of overexpressed proteins and proximity ligation of endogenous proteins (PLA). These results are reminiscent of the effect of TRIM17 on the interaction between TRIM41 or TRIM28 and their respective substrates (Basu-Shrivastava et al, 2021). Further experiments are required to identify the structural determinants of the inhibitory effect of Trim17 on other TRIM proteins.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, Trim17 reduces the interaction between Trim39 and NFATc3, as determined by both co-IP of overexpressed proteins and proximity ligation of endogenous proteins (PLA). These results are reminiscent of the effect of TRIM17 on the interaction between TRIM41 or TRIM28 and their respective substrates (Basu-Shrivastava et al, 2021). Further experiments are required to identify the structural determinants of the inhibitory effect of Trim17 on other TRIM proteins.…”
Section: Discussionmentioning
confidence: 95%
“…In previous work, we have shown that NFATc3 can be SUMOylated on three consensus sites (Mojsa et al, 2015). We have also found that NFATc3 binds to Trim17 (Mojsa et al, 2015), which belongs to a large family of RING-containing E3 ubiquitin-ligases (Basu-Shrivastava et al, 2021). Although its E3 ubiquitin-ligase activity has been confirmed (I.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, TRIM17 can not only promote the degradation of the anti-apoptotic protein MCL1 but also prevent the ubiquitination of other proteins and stabilize them by binding to other TRIM proteins and inhibiting their E3 ubiquitin ligase activity. This dual action confers several pivotal roles to TRIM17 in crucial cellular processes such as apoptosis and autophagy ( Basu-Shrivastava et al, 2021 ). On the contrary, the MAPK family members have a close relationship with other viral signaling pathways, such as NF-κB, PI3K/Akt, and Janus kinase/signal transducer and activator of transcription (JAK-STAT) ( Chander et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The team led by Dr. Solange Desagher at the Institute of Molecular Genetics of Montpellier (IGMM) has been studying the regulation of apoptosis by the E3 ubiquitin-ligase TRIM17 for several years [ 31 ].…”
Section: Team Workmentioning
confidence: 99%